Surgeon’s perceptions on 3D visualization methods in parotid gland tumor surgery - Moll, Manon C. M.; Arends, Coralie; Braun, Loes M. M.; Valstar, Matthijs H.; Smeele, Ludi E.; Zuur, Charlotte L.; van Alphen, Maarten J. A.; Karssemakers, Luc H. (Frontiers in Oncology, 2025)
IntroductionRecent advances in high-resolution MRI and reconstruction techniques offer new opportunities to enhance visualization of the facial nerve and its relationship to parotid tumors in 3D models. The aim of this study is twofold: first, to assess the technical feasibility of generating three-dimensional printed anatomical models from MRI data. Second, to evaluate surgeons’ perceptions of three different visualization methods (3D models on a 2D screen, 3D-printed models, and augmented reality (AR) holograms) to identify the most advantageous method for surgeons performing parotid gland tumor surgery.MethodsFifteen surgeons (otolaryngologists, cranio-maxillofacial, and head and neck) evaluated four clinical Cases using all three visualization methods, in addition to conventional MRI. Participants completed structured questionnaires assessing anatomical clarity, clinical utility, and perceived usefulness and ease of use. Statistical analyses included Friedman and Wilcoxon signed-rank tests, as well as Spearman correlations.ResultsAR holograms achieved the highest median scores for tumor visibility, while all methods performed equally on anatomical landmark visibility. Significant differences in surgical decision-making were observed across cases, with 3D visualizations influencing preferences for surgical approach and perceived risk of facial nerve injury. For intended use, screen-based 3D models and conventional MRI were rated highest for patient consultation and preoperative planning, while intraoperative use received lower scores overall. Perceived usefulness and perceived ease of use scores were highest for AR and 2D screen models. The 3D-printed models were generally rated lower, though some value was noted for patient communication.ConclusionPrinting the facial nerve in relation to a tumor is feasible, despite technical challenges, for which solutions are provided. For clinical care, an anticipated role in preoperative patient consultation and surgical planning of 3D models was favored more than intraoperative use. Among the visualization methods, 3D-printed models were perceived as less effective than those displayed on a 2D screen or in AR. 3D models can serve as valuable adjuncts, but they do not replace conventional MRI.